Julkisen talouden: Rahoituksellinen kestävyys Suomessa - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2011)
This study analyses financial sustainability of the Finnish public sector. Current tax rates are unlikely to yield sufficient tax revenue for financing public expenditure under an ageing population. The estimate of the sustainability gap is 2 1/2 per cent of GDP, for the period 2010 - 2060. The estimate is based on the 2009 population projection by Statistics Finland, where life expectancies are higher and net migration substantially larger than in earlier projections. Health and long-term care costs are modeled to be partly dependent on the proximity to death, and thus grow slowly compared to the growth in the number of old people. The higher initial public debt increases the vulnerability of the public finances to economic and demographic risks.
Keywords: H30; H62; H63; 330; public finance; pensions; health and long-term care; sustainability gap